Changes in the clinical management of 5α-reductase type 2 and 17β-hydroxysteroid dehydrogenase type 3 deficiencies in France - Estelle Bonnet; Mathias Winter; Delphine Mallet; Ingrid Plotton; Claire Bouvattier; Maryse Cartigny; Laetiti Martinerie; Michel Polak; Anne Bachelot; Frédéric Huet; Sabine Baron; Muriel Houang; et al. (Endocrine Connections, 2023)
Objectives: To examine the changes in diagnostic practices and clinical management of patients with 5α-reductase type 2 (SRD5A2) or 17β-hydroxysteroid dehydrogenase type 3 (HSD17B3) deficiency since molecular diagnoses became available. Methods: Clinical, laboratory, and therapeutic data were retrieved from the medical records of 52 patients with a molecular diagnosis of SRD5A2 (n = 31) or HSD17B3 (n = 21) deficiency. Temporal trends regarding age at assessment and initial sex assignment over 1994–2020 were qualitatively analyzed. Age at molecular diagnosis was compared between two subgroups of patients according to their year of birth. Results: Fifty-eight percent (n = 30) patients were diagnosed during the perinatal period, 33% (n = 17) during infancy, and 9% (n = 5) during adolescence or adulthood. Over the studied period, the patients’ age at initial assessment and diagnosis frankly decreased. The median (range) age at diagnostic confirmation was 10.5 (0–53.2) years for patients born before 2007 and 0.4 (0–9.3) years for those born in 2007 or later (P = 0.029). Genetic testing identified 27 different variants for the SRD5A2 gene (30% novel, n = 8) and 18 for the HSD17B3 gene (44% novel, n = 8). Before 2002, most patients were initially assigned as females (95%, n = 19), but this proportion dropped for those born later (44%, n = 14; P < 0.001). The influence of initial genital appearance on these decisions seemingly decreased in the most recent years. Therapeutic interventions differed according to the sex of rearing. Ten percent (n = 2) patients requested female-to-male reassignment during adulthood. Conclusion: This study showed, over the past two decades, a clear trend toward earlier diagnosis and assignment of affected newborns as males.